From war to peace on the Mozambique-Malawi borderland - Englund, Harri (International African library, 2002)
This is a full-length ethnography telling villagers' stories from war to peace in Mozambique. Extended case studies of villages and families on the Mozambique-Malawi borderland form the core of this study.